UJI KUALITAS FISIK AIR BERSIH PADA SARANA AIR BERSIH PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) NAGARI CUPAK KABUPATEN SOLOK - Nisye Frisca Andini (STKIP Pesisir Selatan, 2017)
This study aimed to determine the physical quality of water Pamsimas program based on the nature of physics, chemistry and biology in Nagari Cupak District of Mount Talang in Solok regency. This study was a descriptive observational study to obtain a picture of the physical quality of the water of clean water in Nagari Cupak Program Pamsimas District of Gunung Talang in Solok regency. Total Sampling is the first spring that is the source of water Pamsimas. Physical quality of water adjusted with 492 in 2010. The Minister of Health concerning requirements and Monitoring Water Quality. Results of spring test physical parameters obtained by the odorless, tasteless, color and temperature of 22,6ºC. Chemical parameters springs obtained by the nitrite <0.01 mg / l, iron 0.06 mg / l, hardness of 230 mg / l, manganese <0.25 mg / l, pH of 5.5 mg / l, sulfate 2, 48 mg / l, and an organic substance 1.26 mg / l. Results of laboratory tests for microbiological parameters (total coliforms) in spring is 4 per 100 ml sample.